THE IMPORTANCE OF COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF LUNG CANCER (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Lung cancer is one of the most common and deadly oncological diseases in the world today. According to the World Health Organization (WHO), approximately 2.2 million new cases of lung cancer are recorded annually[7].hu, and more than 1.8 million patients die from this disease annually, which accounts for 18–20% of total cancer deaths. Over the past 10 years, the incidence of lung cancer has increased by 15–20% in some regions. The incidence rate is higher in men than in women, with 60–65% in men and 35–40% in women[3]. Smoking is the main risk factor, and 85–90% of lung cancer patients have a history of smoking. In addition, environmental factors, air pollution, and industrial emissions also play an important role in the development of the disease[2].